2017
DOI: 10.1016/j.flora.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in volatile composition suggests olfactory division of labor within the trap flowers of Aristolochia gigantea

Abstract: Spatial and temporal variation in volatile composition suggests olfactory division of labor within the trap flowers of Aristolochia gigantea.Flora http://dx.doi.org/10.1016/j.flora. 2016.09.005 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 98 publications
(124 reference statements)
1
27
0
Order By: Relevance
“…On traps with rotting meat, C. chani represented only 25% of all flies caught, suggesting that floral volatiles of Rafflesia cantleyi effectively filter the available carrion‐fly pollinator community (Van der Niet et al ., ). The two main compounds of Rafflesia 's floral bouquet are dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS), products of bacterial breakdown of methionine and cysteine in meat, that are typically found in the floral emission of floral carrion mimics (Martin et al ., ; Du Plessis et al ., ; Wee et al ., ). Many species of blowflies are attracted to these volatiles, but Rafflesia flowers also produce terpenoids, benzenoids and fatty acid derivatives, which may have a modulating function leading to higher specificity of the whole bouquet.…”
Section: The Role Of Vocs In Pollinationmentioning
confidence: 99%
“…On traps with rotting meat, C. chani represented only 25% of all flies caught, suggesting that floral volatiles of Rafflesia cantleyi effectively filter the available carrion‐fly pollinator community (Van der Niet et al ., ). The two main compounds of Rafflesia 's floral bouquet are dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS), products of bacterial breakdown of methionine and cysteine in meat, that are typically found in the floral emission of floral carrion mimics (Martin et al ., ; Du Plessis et al ., ; Wee et al ., ). Many species of blowflies are attracted to these volatiles, but Rafflesia flowers also produce terpenoids, benzenoids and fatty acid derivatives, which may have a modulating function leading to higher specificity of the whole bouquet.…”
Section: The Role Of Vocs In Pollinationmentioning
confidence: 99%
“…In the early male phase the pollen is released, but trapping trichomes still block the exit, before they finally shrink and allow pollinators to leave the trap, loaded with pollen (Oelschlägel et al, 2009). Due to their often obvious and strong scents during the female phase, many authors suggested that Aristolochia flowers generally attract their pollinators by floral scent (Vogel, 1978;Hall and Brown, 1993;Bänziger and Disney, 2006;Trujillo and Séric, 2006;Rulik et al, 2008;Martin et al, 2017), which indeed was substantiated by behavioral assays in a few species (Cammerloher, 1923;Daumann, 1971;Oelschlägel et al, 2015). Based on the type of scent released, it is believed that the flowers generally mimic brood-sites of their respective pollinators, such as carrion, feces, decaying plants, or fungi, by chemical deception (Cammerloher, 1923;Vogel, 1978;Proctor et al, 1996;Martin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In some weakly odored species with strongly male-or female-biased pollinator attraction, mimicry of sex pheromones was suggested (Wolda and Sabrosky, 1986;Hall and Brown, 1993). First attempts to identify floral scent compounds in Aristolochia date back almost 100 years (Cammerloher, 1923(Cammerloher, , 1933, but the scent composition was only studied recently in four species by quantitative chemical analytics (Stashenko et al, 2009;Johnson and Jürgens, 2010;Oelschlägel et al, 2015;Martin et al, 2017). Among other compounds (e.g., citral), all these studies identified substances characteristic of brood-site deceptive plants (e.g., dimethyldisulfide), with one exception.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of Ceropegia and Aristolochia attract only a single sex of their pollinator species, suggesting that a critical aspect of mating or brood‐site location behavior is mimicked by floral traits (Berjano et al, 2009; Ollerton et al., 2009), or perhaps a critical fitness‐related resource needed by one sex (J. Ollerton, personal communication). Selective attraction of these pollinators often involves specific volatile compounds, CO 2 , heat, humidity, visual, and tactile traits, some of which may filter out inefficient or antagonistic floral visitors as well as attract effective pollinators (Martin et al., 2017). Table 2 outlines the species richness, known niche dimensions, and economic importance of a subset of dipteran lineages that pollinate Ceropegia and Aristolochia .…”
Section: Coevolution Deceptive Pollination and The Challenges Of Thmentioning
confidence: 99%